Prognostic molecular markers in women aged 35 years or younger with breast cancer: is there a difference from the older patients?. Issue 9 (4th June 2011) - Lin, Ching-Hung; Lu, Yen-Shen; Huang, Chiun-Sheng; Kuo, Kuan-Ting; Wang, Chung-Chieh; You, San-Lin; Lin, Po-Han; Chang, Dwan-Ying; Kuo, Wen-Hung; Chang, King-Jen; Cheng, Ann-Lii
Abstract : Background: Women aged ≤35 years with breast cancer have a poor prognosis, but their prognostic factors have not been clearly defined. Aims: To evaluate whether the molecular markers used in age-unspecified breast cancer could also be applied to women ≤35 years. Methods: Archival tumours from patients aged ≤35 years with stage I–III breast cancer were collected. Oestrogen receptor (ER), progesterone receptor (PR), HER2, Ki67 and P53 protein expression profiles in paraffin-embedded tissue sections were determined by immunohistochemistry. Tumours with an HER2 score of 2+ were further evaluated by fluorescence in situ hybridisation. Mutational analysis of exons 4–9 of the TP53 gene and exons 9 and 20 of the PIK3CA gene was carried out using direct sequencing analysis. Results: 116 patients with a median follow-up duration of 62.7 months were included. In addition to tumour size and axillary lymph node status, univariate analysis showed that high Ki67 expression, ER-negative, HER2 overexpression, and TP53 mutations were associated with shorter overall survival. Multivariate analysis showed that high Ki67 expression (HR=3.93, p=0.005), HER2 overexpression (HR=3.21, p=0.013) and TP53 mutations (HR=4.44, p=0.005) were associated with shorter overall survival. PR expression and PIK3CA mutations were not associated with survival. Conclusions: For women ≤35 years, TP53 mutations, Ki67 and HER2 expressions are strong prognostic factors. The limited prognostic value of hormone receptors suggests that the prognostic markers used in age-unspecified breast cancer may not be completely fit for this population.